009C Sample Final 1, Problem 2

From Math Wiki
Revision as of 17:14, 18 April 2016 by MathAdmin (talk | contribs) (Created page with "<span class="exam"> Find the sum of the following series: ::<span class="exam">a) <math>\sum_{n=0}^{\infty} (-2)^ne^{-n}</math> ::<span class="exam">b) <math>\sum_{n=1}^{\i...")
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search

Find the sum of the following series:

a)
b)
Foundations:  
Recall:
1. For a geometric series with
2. For a telescoping series, we find the sum by first looking at the partial sum
and then calculate

Solution:

(a)

Step 1:  
First, we write
Step 2:  
Since So,

(b)

Step 1:  
This is a telescoping series. First, we find the partial sum of this series.
Let
Then,
Step 2:  
Thus,
Final Answer:  
   (a)
   (b)

Return to Sample Exam